Pengaruh Kepribadian Guru PAI Terhadap Karakter Siswa - Silfa Sofianti; Etep Rohana (Journal of Teacher Training and Educational Research, 2023)
The purpose of this study is to determine whether there is an influence on the personality of Islamic religious education (PAI) teachers on the character of grade XI students at MAS Nurul Iman Bandung. This study used a quantitative approach descriptive method, data collection techniques using questionnaires and observation. Classical Assumption Test, namely: Data Normality Test, Data Linearity Test, Hesterokedasticity Test. And Statistical Analysis i.e. Simple Linear Regression Analysis, Correlation Coefficient Analysis, Descriptive Statistical Analysis and t-Test Hypothesis Testing. The results of this study showed that there was a positive correlation between the personality of PAI teachers (Variable X) with the character of grade XI students (Variable Y) with Sig. (2-tailed) values of 0.036< 0.05. 4) there is a positive influence between the personality of PAI teachers (Variable X) and the character of grade XI students (Variable Y) based on the results of the regression equation Y= a+bX or 16.013+0.576X